1993
DOI: 10.3758/bf03337321
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment proclivities in men and women

Abstract: Sexual harassment proclivities in both men and women were studied in 222 college students. They were administered the newly developed Sexual Harassment Proclivities Scale and their scores were compared with a large number of measures, including sex-role stereotyping, adversarial sexual beliefs, sexual conservatism, acceptance of interpersonal violence, rape myth acceptance, likelihood of rape, acceptance of feminism, empathetic concern, sexual activity, and sexual exploitation. Most of the results were statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 7 publications
3
45
0
Order By: Relevance
“…As another future direction, the ISHMA could be used to continue the exploration of documented links between attitudes toward sexual harassment and actual sexual aggression by men and women (e.g., Bartling and Eisenman 1993;Pryor 1987;Reilly et al 1992). Indeed, Reilly et al (1992) reported that a score on one measure of sexual harassment mythology (the Tolerance for Sexual Harassment Inventory) was the single best predictor of likelihood to rape among male respondents.…”
Section: Directions For Future Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…As another future direction, the ISHMA could be used to continue the exploration of documented links between attitudes toward sexual harassment and actual sexual aggression by men and women (e.g., Bartling and Eisenman 1993;Pryor 1987;Reilly et al 1992). Indeed, Reilly et al (1992) reported that a score on one measure of sexual harassment mythology (the Tolerance for Sexual Harassment Inventory) was the single best predictor of likelihood to rape among male respondents.…”
Section: Directions For Future Researchmentioning
confidence: 93%
“…For example, studies have found that acceptance of sexual harassment myths is positively related to: acceptance of interpersonal violence (Bartling and Eisenman 1993); rape myth acceptance (Bartling and Eisenman 1993;Cowan 2000;Reilly et al 1992); hostility toward women (Cowan 2000;Rosen and Martin 1998); negative attitudes toward gender equity (Wade and BrittanPowell 2001); and traditional attitudes toward women, men, and gender roles (e.g., Bartling and Eisenman 1993;Mazer and Percival 1989;Rosen and Martin 1998;Schneider 1982;Tang et al 1995;Wade and Brittan-Powell 2001). Taken together, this pattern of ideological relationships is similar to that found in the rape myth literature (e.g., Lonsway and Fitzgerald 1994), suggesting a general correspondence of attitudes regarding rape and sexual harassment.…”
Section: Other Beliefs and Attitudesmentioning
confidence: 97%
“…In other words, Burt's measure specifically captures endorsement of the sexual double standard. In past research, sexual conservatism has been associated with support for censoring sexual media (Fisher, Cook, & Shirkey, 1994), victim-blaming for child sexual abuse (Waterman & Foss-Goodman, 1984) and domestic violence (Haj-Yahia, 1998), sexual harassment proclivities (Bartling & Eisenman, 1993), and lower odds of having multiple sexual partners in the last year (Carpenter, Nathanson, & Kim, 2006).…”
Section: Sexual Conservatism As Moderatormentioning
confidence: 98%
“…Feminine traits include nurturance, emotional expressiveness, and selfsubordination. These attitudes result in the stereotypical beliefs that women are inferior to men, particularly in the paid workplace, and that men have the prerogative to initiate sexual behavior of any kind and to use pressure to achieve it when necessary (Bartling and Eisenman, 1993;Walker, Rowe, and Quinsey, 1993). Thus, an environment can be sexist, although the behaviors creating that situation may not constitute the legal definition of sexual harassment.…”
Section: Sexismmentioning
confidence: 99%